Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Ethel Swaggerty Wooden by Grave marker of Edith Duckett Wilson (1921-1940), daughter of Pearl Swaggerty Duckett East Brainard Concord Baptist Cemetery